Oxygen transport to tissue. XXXIX - Halpern, Howard J.; LaManna, Joseph C.; Harrison, D. K. 1951-; Epel, Boris (Springer, 2017)
Chapters 10 and 19 of this book are open access under a CC BY 4.0 license.
Keywords: Oxygen -- Physiological transport -- Congresses.; Tissue respiration -- Congresses.; elektronické knihy; electronic books